Simultaneous Analysis of Fatty Acids in Rubus niveus Thunb. Fruits by HPLC-MS/MS - Caidan, Rezeng; Cairang, Limao; Liubin,; Yourui, Suo (Asian Journal of Chemistry, 2012)
The aim of this study was to optimize the microwave extraction conditions of Rubus niveus Thunb. oil from Qinghai-Tibetan plateau via Box-Behnken design of RSM and then analyze the composition of oil by HPLC-MS/MS using 2-(12-oxobenzo[b]acridin-5(12H)-yl)ethyl-4-toluene-sulfonate as labeling reagent. The optimum microwave extraction conditions were as follows: irradiation power 437 W, extraction temperature 75 ºC and extraction time 12 min. Under these optimized conditions, the maximum oil extraction yield was 5.83 %. All fatty acid derivates had excellent linear responses with correlation coefficients greater than 0.9990. Detection limits (at signal-to-noise of 3:1) were 18.42 to 32.39 pmol. The results indicate that the predominant fatty acids (C10-C22) were 16:0, 18:2, 18:3, 18:0 and 22:0 in total fatty acids. And the unsaturated fatty acids were 18:3, 18:2, 18:1 and 20:4 and reached up to 40.54 % of the total mass contents of fatty acids (C10-C22) in Rubus niveus Thunb. from Qinghai-Tibetan plateau.